Angiotensin 1-7 and Mas decrease thrombosis in Bdkrb2(−/−) mice by increasing NO and prostacyclin to reduce platelet spreading and glycoprotein VI activation - Fang, Chao (American Society of Hematology, 2013)
Bradykinin B2 receptor–deleted mice (Bdkrb2(−/−)) have delayed carotid artery thrombosis times and prolonged tail bleeding time resulting from elevated angiotensin II (AngII) and angiotensin receptor 2 (AT2R) producing increased plasma nitric oxide (NO) and prostacyclin. Bdkrb2(−/−) also have elevated plasma angiotensin-(1-7) and messenger RNA and protein for its receptor Mas. Blockade of Mas with its antagonist A-779 in Bdkrb2(−/−) shortens thrombosis times (58 ± 4 minutes to 38 ± 4 minutes) and bleeding times (170 ± 13 seconds to 88 ± 8 seconds) and lowers plasma nitrate (22 ± 4 μM to 15 ± 5 μM), and 6-keto-PGF(1α) (259 ± 103 pg/mL to 132 ± 58 pg/mL). Bdkrb2(−/−) platelets express increased NO, guanosine 3′,5′-cyclic monophosphate, and cyclic adenosine monophosphate with reduced spreading on collagen, collagen peptide GFOGER, or fibrinogen. In vivo A-779 or combined L-NAME and nimesulide treatment corrects it. Bdkrb2(−/−) platelets have reduced collagen-related peptide–induced integrin α(2b)β(3) activation and P-selectin expression that are partially corrected by in vivo A-779, nimesulide, or L-NAME. Bone marrow transplantations show that the platelet phenotype and thrombosis time depends on the host rather than donor bone marrow progenitors. Transplantation of wild-type bone marrow into Bdkrb2(−/−) hosts produces platelets with a spreading defect and delayed thrombosis times. In Bdkrb2(−/−), combined AT2R and Mas overexpression produce elevated plasma prostacyclin and NO leading to acquired platelet function defects and thrombosis delay.